The internationalization process of the largest Baltic corporations - Liuhto, Kari; Jumpponen, Jari (Journal of Business Economics and Management, 2003)
A relatively high percentage of Baltic corporations have already started their operations abroad, over 40% of the companies studied. It is surprising that the approaching EU membership docs not seem to be the driving force of the Baltic corporations’ internationalization, though the EU is clearly the major export destination. The empirical evidence shows that the operations of the Baltic companies in foreign markets, have concentrated on the ex‐CMEA countries, especially on the former USSR. The empirical data indicates that most of the operations abroad are related to marketing, such as the foundation of their own representative office or their own sales unit in a foreign market.First Published Online: 14 Oct 2010